How the Earth works - Farndon, John.; Dunning, Mike (Pleasantville, N.Y. : Reader's Digest Association, 1992)
Experiments and projects explore the earth's structure, features, and changing landscape.
Includes index.
Subtitle on cover: 100 ways parents and kids can share the secrets of the earth.
6.7
6.7
5-8.
5-8
Keywords: Geophysics -- Juvenile literature; Geophysics -- Experiments -- Juvenile literature; Experiments; Geophysics; Geophysics -- Experiments; Geophysics; Geophysics -- Experiments; Earth -- Juvenile literature; Earth -- Experiments -- Juvenile literature; Earth; Earth -- Experiments; Earth; Earth -- Experiments